Structural and functional analysis of a cloned segment of Escherichia coli DNA that specifies proteins of a C4 pathway of serine biosynthesis. - Ravnikar, P D (1987)
The plasmid pDR121 is a pBR322 derivative that contains a 3.7-kilobase-pair EcoRI fragment of DNA from the 81.2-min region of the Escherichia coli chromosome. The genomic insert encodes threonine dehydrogenase and at least one other protein. Several physical and kinetic properties of threonine dehydrogenase, overproduced in cells harboring pDR121, are identical to those of pure threonine dehydrogenase from a haploid mutant of E. coli K-12 that produces this enzyme constitutively. Tester strains with serB or glyA mutations harboring pDR121 are prototrophs. The ability to confer prototrophy on such tester strains is associated with elevated levels of threonine dehydrogenase. The functional roles of various segments of the 3.7-kilobase-pair insert of pDR121 were analyzed by constructing specific deletions and insertions. Certain subclones retained the ability to specify threonine dehydrogenase without conferring prototrophy on tester strains. This suggests that at least one other protein encoded within pDR121 plays an essential role in the conversion of threonine to serine.